The Green Bonds Issuance Role In Reducing Carbon Emission: Evidence From ASEAN - Robert Chowiendo; Yunieta Anny Nainggolan; Isrochmani Murtaqi (Journal Integration of Management Studies, 2025)
The global initiative to reduce carbon emissions has accelerated in line with the Paris Agreement’s target to limit global warming to below 2°C. Yet, transitioning to a low-carbon economy remains financially challenging, with limited funding channels for decarbonization. Green bonds have emerged as a key financing mechanism, mobilizing capital toward clean energy, energy efficiency, and environmentally sustainable projects. This study offers novel empirical evidence on the role of green bonds in mitigating carbon emissions within ASEAN—an economically dynamic yet fossil fuel-dependent region with substantial greenhouse gas outputs. Leveraging panel data from 2019 to 2023 across publicly listed firms in ASEAN countries, this research applies multiple regression analysis to examine the effects of Green Bonds (GB), Firm Size (FS), and Gross Domestic Product (GDP) on Carbon Emissions (CE). The findings reveal a statistically significant negative relationship between green bond issuance and carbon emissions, indicating that increased green bond financing contributes to emission reductions. Firm size is also found to influence emissions negatively, whereas GDP has no statistically significant impact. The study provides practical insights for policymakers and investors by highlighting the effectiveness of green bonds as a sustainable financing tool in the ASEAN context.